2021
DOI: 10.2514/1.j060134
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic Assessment of Performance of Overtip Liners in Reducing Airfoil Noise

Abstract: The reduction of fan broadband noise in the next generation of Ultra-High By-pass-Ratio (UHBR) engines remains a key technology challenge for the foreseeable future. The Over-Tip-Rotor (OTR) liner concept has been studied as a technology with the potential to further reduce fan noise and significant noise reductions have been measured. This paper describes a fundamental experimental evaluation that represents the Over-Tip-Rotor liner as a static airfoil with its tip located over a flat plate containing a flush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In contrast, the power radiated to the 'farfield' is finite in all cases and generally reduces when the source is located closer to the lined wall. This corresponds to experimental observations in [28,29,30].…”
Section: The Effect Of the Modal Truncation Parameter (Cor) On The So...supporting
confidence: 90%
“…In contrast, the power radiated to the 'farfield' is finite in all cases and generally reduces when the source is located closer to the lined wall. This corresponds to experimental observations in [28,29,30].…”
Section: The Effect Of the Modal Truncation Parameter (Cor) On The So...supporting
confidence: 90%
“…Over-the-rotor liners An important noise component in the turbofan engines is that which is generated by the interaction of the flow with the rotor blades and stator vanes. In particular, the tip clearance is a relevant source of the self-noise because the pressure difference between the two sides of a blade starts a tip-leakage vortex, which interacts with the blade tip edge [22,23]. To this end, the over-the-tip liners (OTLs) have been investigated during the past decades as a technology with the potential to attenuate the fan noise in turbofan engines [24].…”
Section: A Reduction Of Noise At the Sourcementioning
confidence: 99%
“…The set-up of the OTL in the demonstrator is based on the wind tunnel experiments conducted by Palleja-Cabre et al [22], in which the rotor and OTL are represented by a static airfoil with its tip located over a flat plate containing a flush-mounted liner insert and separated from the airfoil tip by a small gap of 5 mm. On the exterior wall of the test section, two hinges allow easy swapping of two different panels, i.e., a hard wall or a liner in the over-tip position with a surface of 0.21 m × 0.12 m. An elastic O-ring is used to seal the panels to the test section.…”
Section: Otlmentioning
confidence: 99%
See 1 more Smart Citation
“…Although that work does not involve OTR liners, it shows that the coupling of the liner and nearby sound sources should be considered when targeting the liner optimum impedance. A recent study on the reduction of tip noise sources with an over-tip liner has been reported in [7] using a static aerofoil. It shows that the noise reduction benefits of over-tip liners are greater when the noise sources are close to the liner surface.…”
Section: Introductionmentioning
confidence: 99%